2021
DOI: 10.1111/ppc.12928
|View full text |Cite
|
Sign up to set email alerts
|

Female gender and low physical activity are risk factors for academic stress in incoming nursing students

Abstract: Purpose: Nursing students suffer from stress more frequently than other students.The objective was to analyze the academic stressors that most affect new nursing students. Design and Methods:A cross-sectional study on new nursing students.Findings: Two hundred and eighty-two students, 78% women, mean age of 21.46 (6.1) years. Giving presentations in class and lack of time for homework are the items that cause the greatest academic stress. Women had higher levels of academic stress, and higher levels of physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 44 publications
1
8
1
5
Order By: Relevance
“…They express their feelings of stress more frequently than men. Therefore, it cannot be determined whether women actually experience more academic stress than men or whether the discrepancies can be explained by women's greater propensity to report their experiences (Chust-Hernández et al, 2021) In the current study, a non-significant relationship was found between physical activity level and perceived academic stress. Stress levels were similar in both groups.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…They express their feelings of stress more frequently than men. Therefore, it cannot be determined whether women actually experience more academic stress than men or whether the discrepancies can be explained by women's greater propensity to report their experiences (Chust-Hernández et al, 2021) In the current study, a non-significant relationship was found between physical activity level and perceived academic stress. Stress levels were similar in both groups.…”
Section: Discussioncontrasting
confidence: 74%
“…Female gender appears to be a factor for academic stress (Chust-Hernández et al, 2021). They sensitive more to stress.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…De los tres, se ha evidenciado que son los estresores académicos los que más afectan al estudiantado universitario (Fernández-Rodríguez et al, 2019;Reis et al, 2021). Algunas de las situaciones académicas que más estrés provocan a los estudiantes son la falta de tiempo para completar las tareas académicas, las exposiciones orales, los exámenes y la sobrecarga académica (Chust-Hernández et al, 2021;Fernández-Rodríguez et al, 2019;García-Ros et al, 2012;Souto et al, 2019).…”
Section: Introductionunclassified